PENERAPAN METODE BLENDED LEARNING DI MASA PANDEMI COVID-19 PADA MATA PELAJARAN FISIKA MATERI “PENGUKURAN” PADA SISWA KELAS X SMK NEGERI 1 SITINJO - Tiarna Samosir (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
Based on observations indicate that the critical thinking skills of students is still low. Therefore, the critical thinking skills students need to be improved, especially in the measurement  material, then applied the method of Blended learning . This purposes of this research is to improve learning result on physics education subject  through Blended learning method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class X Vocational High School State 1 Sitinjo which amounted to 16 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the Blended learning method of physical education can improve learning result of under pass which characterized by increased mastery learning students, namely cycle I (68,75%), the cycle II (87,5%) and complete learn the clasical equal to 87,5% in cycle II.